Managing the capital investment projects: theory and practice - AFRĂSINEI-ZEVOIANU, Cătălin (Presa Universitară Clujeană, 2024)
The term "investments" has many meanings and contents in economic theory. Essentially, the concept of "investments" can be approached in a broader/extended way, the economic way, as well as in a narrower orientation, the economic-financial way.